MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA PURWABAKTI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Putri, Hani Cahyani (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This community service aims to increase public knowledge and understanding of sharia banking and reduce the use of ribawi banking by the public. The subject of this social service is Purwabakti Village, Pamijahan District, Bogor Regency, West Java Province. In this community service, according to the method field research, it provides an impact on the community and new information in choosing the right sharia banking to avoid banks with high interest rates. With this community service, it can be concluded that it is important to provide education to the community in order to provide a clear understanding to the local community.